Minimization of Starting Energy Loss of Three Phase Induction Motors based on Particle Swarm Optimization and Neuro Fuzzy Network - Mahmoud M. Elkholy; Mohamed A. Elhameed (Institute of Advanced Engineering and Science, 2016)
The purpose of this paper is to minimize energy losses consumed by the induction motor during starting with wide range of load torque from no load to full load. This will limit the temperature rise and allows for more numbers of starting during a definite time. Starting energy losses minimization is achieved by controlling the rate of increasing voltage and frequency to start induction motor under certain load torque within a definite starting time. Optimal voltage and frequency are obtained by particle swarm optimization (PSO) tool according to load torque. Then, outputs of the PSO are used to design a neuro-fuzzy controller to control the output voltage and frequency of the inverter during starting for each load torque. The starting characteristics using proposed method are compared to starting characteristics using direct on line method and V/F method. A complete model of the system is developed using SIMULINK/MATLAB.